A laboratory work to introduce Biochemistry undergraduate students to basic enzyme kinetics -alkaline phosphatase as a model - Miquet, Johanna Gabriela (2019)
Enzyme kinetics is an essential topic in undergraduate Biochemistry courses. A laboratory work that covers the principal basic concepts of enzyme kinetics in steady state is presented. The alkaline phosphatase catalyzed reaction of phenyl-phosphate hydrolysis was studied as a model. The laboratory experience was designed to reinforce the concepts of initial velocity dependence on substrate and enzyme concentration, and to highlight the importance of the accurate determination of initial reaction rate. The laboratory work consists in two parts, in which students first determine the enzyme concentration and the time to be used in the following session to obtain the kinetic parameters (KM and Vmax ) by non-lineal fitting of the Michaelis-Menten equation to the initial velocity dependence with substrate concentration results. The experimental methodology is robust, the cost per student is low and the equipment and reagents used are of easy access.